N-Cadherin as An Important Marker in Colorectal Cancer: An investigation of b-Catenin and Cadherin Expressions of SW-480 and HCT-116 Cell Lines - Winarko Luminturahardjo; Djoko Wahono Soeatmadji; Karyono Mintaroem; Pudji Rahajoe; Ferry Sandra (The Indonesian Biomedical Journal, 2021)
BACKGROUND: The absence of potential biomarkers to detect the metastatic process at an early stage will consequently delay colorectal cancer (CRC) treatment. Some biomarkers including β-Catenin, E-Cadherin and N-Cadherin have been suggested as potential markers. However, there were opposite reports regarding expressions of these markers. Therefore, current study was conducted using CRC cell lines for early stage (SW-480 cells) and late stage (HCT-116 cells) of CRC.METHODS: SW-480 and HCT-116 cells were cultured and seeded on coverslip glasses for immunofluorescence staining to detect β-Catenin, E-cadherin, and N-cadherin. Expressions of β-Catenin, E-cadherin, and N-cadherin were observed and documented under a fluorescent microscope and analyzed with Image J software. Measured results were then statistically analyzed. RESULTS: All β-catenin, E-Cadherin and N-Cadherin expressions were observed in SW-480 and HCT-116 cells. β-catenin MFI averages of SW-480 (47.157±3.479) and HCT-116 (47.240±4.107) cells were similar. E-Cadherin MFI average of SW-480 cells (45.104±4.107) was higher than the one of HCT-116 cells (40.191±3.702). N-Cadherin MFI average of HCT-116 cells (43.702±8.219) was significantly higher (p=0.009) than the one of SW-480 cells (72.506±5.297).CONCLUSION: Taken together, N-Cadherin could be suggested as an important metastasis marker in CRC since the N-Cadherin expression was significantly higher in HCT-116 cells as the late-stage CRC model than SW-480 as the early-stage of CRC model. Further research is still needed by comparing several biomarkers from various clinical samples at all clinical stages of CRC.KEYWORDS: CRC, β-Catenin, E-Cadherin, N-Cadherin, Metastasis, Biomarker